THE EFFECT OF ENVIRONMENTAL PERFORMANCE AND CORPORATE SOCIAL RESPONSIBILITY ON THE FINANCIAL PERFORMANCE OF MANUFACTURING COMPANIES IN THE PLASTIC AND PACKAGING INDUSTRY SUB SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE - Dea Laila Puspita; Debbi Chyntia Ovami (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Abstract*